Design and Evaluation of a Virtual Restorative Walk With Room-Scale Virtual Reality and Impossible Spaces - Rockstroh, Christoph; Blum, Johannes; Hardt, Véronique; Göritz, Anja S. (Frontiers in Virtual Reality, 2020)
Nature walks are an effective and popular means to replenish fatigued mental resources. Alas, nature walks are not always accessible due to a lack of time or limited availability. We report on the design and pilot test of a room-scale virtual reality (VR) application that makes use of actual walking and impossible spaces to simulate dynamic restorative walks. We conducted a randomized controlled experiment in VR using a between-subjects design. Thirty-one participants went for an 8-minute virtual walk either in a fixed virtual restorative environment (control condition) or in the proposed dynamic virtual restorative environment (treatment condition). The treatment condition with the proposed room-scale approach yielded increased user involvement, higher present moment awareness, increased perceived restorativeness of the experience, better subjective restoration, and an improved positive affect. Behavioral analysis showed that the proposed approach led to a reduced walking speed over the course of the walking exercise. The results suggest that room-scale VR in conjunction with virtual restorative environments and impossible spaces can be used to create sophisticated virtual restorative walks in confined spaces. Future research and development are needed to further establish the effects, to identify moderating and mediating factors and to investigate such VR applications in relevant real-world contexts.